A. I. Conejo, Colores, Barcelona, La Garúa Libros, 2007, 72 pp. - Martínez Fernández, José Enrique (Estudios Humanísticos. Filología, 2008)
A. I. Conejo, Colores, Barcelona, La Garúa Libros, 2007, 72 pp.